2020
DOI: 10.5937/fme2004889g
|View full text |Cite
|
Sign up to set email alerts
|

Environmental control and test dynamic control of the engine output parameters

Abstract: In modern transport, environmental control plays a key role in shaping the strategy for managing the technical condition of nodes and systems. The first step in reducing the toxicity of exhaust gas emissions was the introduction of Euro standards, successively from Euro-0 to Euro-6. Accompanying the appearance of Euro standards, exhaust systems were supplemented with catalytic converters, which deactivated most of the harmful emissions. Oxygen sensors also began to play a key role, the installation of which re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Emissions from marine diesel engines are one of the main pollutants of the Arctic territories. Fine particulate matter (FPM) in diesel and gasoline engine exhaust is associated with an increase in various diseases [4,25]. Wu, D. et al [26] showed that FPMs are potentially hazardous and highlighted the importance of assessing the health risks posed by FPMs in exhaust gases.…”
Section: Emissions From Marine Diesel and Potential Measures To Reduc...mentioning
confidence: 99%
See 1 more Smart Citation
“…Emissions from marine diesel engines are one of the main pollutants of the Arctic territories. Fine particulate matter (FPM) in diesel and gasoline engine exhaust is associated with an increase in various diseases [4,25]. Wu, D. et al [26] showed that FPMs are potentially hazardous and highlighted the importance of assessing the health risks posed by FPMs in exhaust gases.…”
Section: Emissions From Marine Diesel and Potential Measures To Reduc...mentioning
confidence: 99%
“…Marine basins and coastal areas are subject to ecological impact: due to mining on the shelf, oil and oil product spills during the transportation of goods and fishing activities, etc. Among the atmospheric air pollutants, black carbon (soot), which is emitted when using marine diesel fuel, has a particularly strong negative impact [4,5]. For the Arctic territories, this impact is associated not only with an increase in population diseases but also with snow and ice pollution, which negatively affects ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Within the automotive industry, platinum group metals (PGMs) have found extensive utilization as catalysts for exhaust gas treatment, a practice that has gained prominence since the 1970s [ 3 ]. This surge in PGM application is primarily caused by the necessity to meet strict environmental requirements, exemplified by regulations like the Euro standards [ 4 ]. Conventional PGM extraction from ores involves labor-intensive processes, underscoring the need for more ecologically sustainable, convenient methodologies for obtaining catalytic systems.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of reducing toxicity is addressed in a variety of ways. There have been a number of studies relating to the addition of small amounts of water into the ICE combustion chamber [4][5][6]. Cylinder deactivation [7][8][9][10][11] methods are also fairly widely known.…”
Section: Introductionmentioning
confidence: 99%